The Influence of Laboratory Diagnostics on Nursing Management of Respiratory Tract Infections: Review of Current Technologies and Their Implications for Patient Care - Alsharari, Mohammed Madallah S; Alsharari, Mohammed Atallah Hayshan; Alsharari, Ghazi Salman Saleem; Alruwaili, Ibtisam Ibrahim Rahil; Alsharari, Ahmed Aqeel Mufadhi; Alshrari, Nader Sliman F; Maashi, Afrah Nasser Mosa; Mutee, Hind Gassem Habib; Alsharari, Muteb Mutlaq Ghafil; Alsharari, Ibrahim Sabih Basheer (Journal of Ecohumanism, 2024)
Background: Respiratory tract infections (RTIs) represent a significant public health challenge due to their high prevalence and associated morbidity and mortality rates. Accurate and timely laboratory diagnostics are crucial for effective nursing management of these infections, ensuring appropriate treatment and minimizing the misuse of antimicrobials. Methods: This review synthesizes current literature on laboratory diagnostic technologies for RTIs, emphasizing the role of syndromic panels and molecular techniques in detecting bacterial and viral pathogens. It discusses the epidemiological trends of RTIs, diagnostic methodologies, and the implications for nursing management in clinical settings. Results: Recent advancements in diagnostic technology, particularly molecular methods, have enhanced the accuracy and speed of identifying RTIs, which is essential for effective patient management. Syndromic panels allow for the simultaneous detection of multiple pathogens, facilitating rapid clinical decision-making. However, challenges remain, including the cost of molecular assays and the need for appropriate specimen collection and handling to ensure diagnostic reliability. Conclusion: The integration of advanced laboratory diagnostics into nursing practice is vital for improving outcomes in patients with RTIs. Nurses play a critical role in the diagnostic process, from specimen collection to interpreting results, which informs treatment decisions. Ongoing education and training are necessary to equip nursing professionals with the skills needed to utilize these advancements effectively.